Smart cities for local growth. Experiences in Liguria, Italy. The case studies of the municipalities of Savona and La Spezia. - Sergi, Giovanni; Rosasco, Paolo; Bianchi, Chiara (Springer, 2018)
The main results of this paper will be the explanation of methods and contents of the experiences in Liguria aiming at converting a consolidated urban organism into a Smart City. Specific attention is paid to the experience in the municipalities of Savona and La Spezia. We can say that, similarly to what happened in the past years in many European and North American cities, the first projects related to the Smart City in Italy concern the possibility of introducing new technologies to make components of the urban system more efficient. In a second step, local institutions identified new technologies as one of the tools to develop new models of economic development and welfare. For some years in Italy, there has been a debate over the issue of the Smart City within research institutions, universities and leading companies in the sector of advanced technologies. This debate has highlighted both some of the most interesting experiences in Italy and the difficulty to develop a holistic approach to this complex issue. The ways in which regional, provincial, metropolitan and municipal administrations cooperate with companies in the ICT sector have changed considerably. Besides proposing technologically-advanced products for public administrations, these companies should undertake to work with universities and research centers in order to promote the growth of the economic system and of local employment through a holistic approach.
Keywords: Stadtentwicklungsplanung; Smart City; Wirtschaftsentwicklung; Digitalisierung; Öffentliche Verwaltung; Kommunale Wirtschaftspolitik; Regionale Wirtschaftspolitik; Regionalwirtschaft; Stadtwirtschaft